Bridging Religiosity, Trust, and Service Quality: The Role of Customer Intention in Driving Saving Decisions - Ahmad, Yusuf Falaqi; Supriyanto, Achmad Sani; Ekowati, Vivin Maharani; Julaihah, Umi; Masyhuri; Johari, Fuadah Binti (Jurnal Aplikasi Manajemen, 2025)
Technological advances have impacted intense business competition in the banking world, requiring all banks to compete in updating systems to maintain service quality, which is essential to a business' success. Factors influencing the decision to save in syariah banks are religiosity, trust, and service quality. This study aims to examine and analyze the influence of religiosity, trust, and service quality on the saving decisions of Islamic students, both directly and indirectly through intention. The population in this study comprises Islamic students at PTKI (Islamic Higher Education Institutions) in Malang. The study uses a sample of 240 students from PTKI Malang, selected through purposive sampling based on criteria such as a minimum grade of A for PTKI and students enrolled in the Islamic banking study program. This study employs quantitative analysis with an explanatory study approach. Data were analyzed using path analysis to test the significance and direct and indirect effects using SPSS 24 software. The study's results indicate that religiosity, trust, service quality, and intention significantly influence saving decisions. However, intention does not mediate the influence of religiosity, trust, and service quality on saving decisions. The findings from this study could be applied to enhance the decision to save by building service quality, customer trust, and sharing the bank’s reputation, so that they receive credible information from the bank.